POWERLIFTING SESSIONS PROMOTE SIGNIFICANT POST-EXERCISE HYPOTENSION - João,Gustavo Allegretti (2017)
ABSTRACT Introduction: Powerlifting (PWL) is a worldwide method, frequently used in resistance training programs. However, the relationship between cardiovascular responses and PWL is still unclear in the literature. Objective: To evaluate acute cardiovascular overload and post-exercise hypotension (PEH) after acute powerlifting exercise session in subjects with experience in the modality. Methods: Nine powerlifting athletes (34 ± 5 years) participated voluntarily in this study. The following exercises were used in the session: squat, bench press and deadlift (95% of 1 RM, 2 to 5 repetitions). The anthropometric parameters and blood pressure (systolic, diastolic and mean) were evaluated immediately, 5', 10', 30', 60' and 24 hours after the exercise session with a non-invasive automatic pressure monitor. Results: Significant differences (p<0.05) were found between rest and immediately after exercise on systolic (135 ± 6 vs. 153 ± 10 mmHg) and mean (102 ± 3 vs. 108 ± 3 mmHg) blood pressures, but no difference was found at diastolic (85 ± 3 vs. 85 ± 4 mmHg) blood pressure. Additionally, the increase in systolic pressure did not reach values considered as a risk of cardiovascular overload. Significant PEH was found after 60 minutes (systolic: -12 ± 12%, diastolic: -5 ± 6% and mean: -7 ± 5%) and 24 hours after PWL session (systolic: -5 ± 4%, diastolic: -8 ± 4% and mean: -7 ± 3%). Conclusion: Our data demonstrated that a PWL session does not increase systolic blood pressure up to the risk range and promotes PEH after 60 minutes of exercise and that this cardiovascular response persisted after 24 hours post-exertion in powerlifting athletes.